Krabbe's globoid cell leucodystrophy. Studies on galactosylceramide beta-galactosidase and non-specific beta-galactosidase of leucocytes, cultured skin fibroblasts, and amniotic fluid cells. - Besley, G T (1976)
Galactosylceramide beta-galactosidase (cerebrosidase) and nonspecific beta-galactosidase activities were measured in both cultured skin fibroblasts and leucocytes from a family with Krabbe's globoid cell leucodystrophy (GLD). The activities of these enzymes were also determined in cultured skin fibroblasts of a patient with GM1 gangliosidosis and in cultured amniotic fluid cells. While cerebrosidase activity was deficient in GLD fibroblasts and leucocytes, its activity in GM1 gangliosidosis fibroblasts was increased. Two forms of each enzyme were found on isoelectric focusing, but in the GM1 gangliosidosis fibroblasts, cerebrosidase activity occurred as a single but intermediate peak. The use of cultured cells in assessing isoenzyme abnormalities associated with certain neurolipidoses is discussed.